A risk assessment of cyanobacteria and cyanotoxins in Hartbeespoort Dam - Kuiper, Cassidy (My University, 2021)
Water is an important natural resource for the human population. Nutrient build-up through cultural eutrophication, warm water temperatures, and high insolation in Hartbeespoort Dam have historically resulted in the dam becoming hypertrophic accompanied by frequent and persistent cyanobacterial blooms. The decreased quality of water in Hartbeespoort Dam is a public health threat as water from the dam is used for irrigation, recreational activities, and is a source of potable water. Many cyanobacteria genera produce toxins (cyanotoxins) that pose a health risk to animals and humans. Cyanobacterial bloom formation is a function of complex interactions between system-specific physical, chemical, and biological factors occurring simultaneously in freshwater bodies. The aim of this study was to determine the human health risk associated with exposure to cyanotoxins produced by cyanobacteria based on an ecological health assessment of Hartbeespoort Dam. Water quality was determined based on in situ physico-chemical measurements and laboratory-based measurements of nutrient concentrations. Additionally, phytoplankton community structure and biomass, and total microcystin concentrations were determined. The rapidly growing population and poor water management in the Gauteng Province has resulted in a build-up of nutrients in Hartbeespoort Dam. Inorganic nutrient concentrations increased as the study progressed into winter positively correlating to cyanobacteria cell density, reaching a maximum density during mid-winter. Dissolved oxygen correlated to the photosynthetic activity of phytoplankton instead of water temperature changes in the dam. Additionally, microcystin concentration increased as the study progressed into winter due to a poor dilution capacity in Hartbeespoort Dam. It was assumed that condition required for bloom formation did not occur simultaneously in Hartbeespoort Dam during the study. Water hyacinth in Hartbeespoort Dam appears to control phytoplankton and cyanobacterial growth thus preventing bloom formation in the dam as it is a useful tool for removing excess inorganic nutrients from eutrophic waterbodies. Microcystin concentration in Hartbeespoort Dam, however, exceeded the recommended guidelines for recreational waters. Hartbeespoort Dam therefore posed a significant risk to human health, and it was advised to approach the dam with caution
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Environmental Sciences to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2021